Clinical outcomes of critical limb ischemia in Buerger disease: A contemporary analysis from an academic referral center in Jordan - Qusai Aljarrah; Mohamad Al-Badaineh; Hammam Bani Salman; Nizar R. Alwaqfi; Sohail Bakkar; Mahmoud Megdadi; Khalid A. Kheirallah; Mohammed Z. Allouh (PLoS ONE, 2026)
Objective Buerger disease (BD), thromboangiitis obliterans , is a rare occlusive peripheral arterial disease affecting young smokers. To date, no study has investigated the burden of this disease in Jordan. This study aimed to assess the clinical course and factors associated with adverse outcomes of BD patients with critical limb ischemia (CLI) in Jordan. Methods The medical records of all patients with BD who presented with CLI at King Abdullah University Hospital in Jordan between January 2015 and January 2024 were retrospectively retrieved. The epidemiological profile of retrieved cases was collected along with the course of treatment, adverse events, and outcome. Statistical analyses were performed to assess the relationships between patient presentation, treatment course, and outcome. Results The study comprised 41 BD patients with Rutherford categories (RC) (IV-VI). The majority were males (95.1%) in their third decade (51.2%). Most patients (92.7%) presented with ischemic ulcerations (RC V, VI). A multivariable regression model revealed that increased C-reactive protein levels (OR = 1.044, 95% CI [1.003, 1.087], p = 0.035), gangrene at presentation (RC VI) (OR = 11.545, 95% CI [1.444, 92.332], p = 0.021), and limb infections at admission (OR = 7.745, 95% CI [1.182, 50.755], p = 0.033) were practical predictors of ending up with major limb amputation. Conclusion In Jordan, BD is associated with a high rate of amputation, which imposes considerable financial and social burdens. Prompt recognition, early management, and stringent smoking cessation measures are imperative to slowing disease progression.